1959
DOI: 10.1002/j.1537-2197.1959.tb07054.x
|View full text |Cite
|
Sign up to set email alerts
|

Three Chlorophyceae From Alabama Soil

Abstract: Deason, Temd R. (U. Texas, Austin.) Three Chlorophyceae from Alabama soil. Amer. Jour. Bot. 46(8): 572–578. Illus. 1959.— Three new algae from Alabama soil are described as follows: Spongiococcum gen. nov., with 2 species, S. tetrasporum sp. nov. and S. alabamense sp. nov. The distinguishing attributes of the genus Spongiococcum are: (1) possession of a sponge‐like plastid; (2) presence of pyrenoids; and (3) Chlamydomonas‐type zoospores. The description of the genus Chlorosarcina Gerneck is emended with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…There are comparable species in the Chlorosarcinopsis but the cells in this genus possess pyrenoids. The plant has tentatively been placed in the genus Chlorosarcina because it has various characteristics in common with those of Chlorosarcina stigmutica Deason (1959) but it must be borne in mind that there is considerable controversy surrounding C. stigmutica (Sluiman & Blommers, 1990) and the genus Chlorosarcina itself. Confirmation that the alga belongs in the Chlorophyceae would require a study of the ultrastructure, especially of the flagellar basal apparatus of the zoospores.…”
Section: Chlorosarcina Spmentioning
confidence: 99%
“…There are comparable species in the Chlorosarcinopsis but the cells in this genus possess pyrenoids. The plant has tentatively been placed in the genus Chlorosarcina because it has various characteristics in common with those of Chlorosarcina stigmutica Deason (1959) but it must be borne in mind that there is considerable controversy surrounding C. stigmutica (Sluiman & Blommers, 1990) and the genus Chlorosarcina itself. Confirmation that the alga belongs in the Chlorophyceae would require a study of the ultrastructure, especially of the flagellar basal apparatus of the zoospores.…”
Section: Chlorosarcina Spmentioning
confidence: 99%
“…Originally, the genus Chlorosarcina was described as containing 3 species (C. brevispinosa, C. longispinosa, and C. stigmatica), and it was placed in the class Chlorophyceae with C. stigmatica as the type species (Deason 1959). Subsequently, Deason and Floyd (1987) separated C. stigmatica from C. longispinosa and C. brevispinosa based on ultrastructural characteristics and placed C. longispinosa and C. brevispinosa in the Pleurastrophyceae (now Trebouxiophyceae) based on several characteristics, including counterclockwise orientation of the flagellar apparatus components.…”
mentioning
confidence: 99%
“…This species has been found among aerial algae (Deason 1959). In this study, this species was found in a wide range of habitats where the light intensity and humidity ranged from 3,915-48,000 lux and 26-65%, respectively (Table 2).…”
Section: Spongiococcum Tetrasporum Deason (Fig 2)mentioning
confidence: 68%
“…This genus was named by Deason in 1959, and newly recorded in this study in Korea. Deason (1959) isolated the genus Spongiococcum from a soil sample in Alabama, USA, and described it as a sponge-like plastid, with a pyrenoid and Chlamydomonas-type zoospore.…”
Section: Family Chlorococcaceae Subfamily Spongiococcoideae Genus Spomentioning
confidence: 80%
See 1 more Smart Citation